Analisis Proses Rekrutmen dan Seleksi Karyawan Pada PT. Dua Kelinci Kabupaten Pati - Niki Kosasih; Muhammad Kohar (CITRA EKONOMI, 2021)
This study entitled "Analysis of Recruitment Process and Selection of Employees at PT. Dua Kelinci Kabupaten Pati ", which aims to find out how the employee recruitment process at PT. Dua Kelinci Kabupaten Pati, to find out how the employee selection process at PT. Dua Kelinci Kabupaten Pati, to analyze the employee recruitment process at PT. Dua Kelinci Kabupaten pati. and to analyze the employee selection process at PT. Dua Kelinci Kabupaten Pati. This research was conducted at PT. Dua Kelinci Kabupaten Pati. Methods of analysis Data processing is carried out by qualitative descriptive analysis method, which is to compare existing theories of relevance to the implementation found in the company. The results of this study indicate that PT. Dua Kelinci Kabupaten Pati conduct two types of recruitment, namely Internal Recruitment (from within the company) and External Recruitment (from outside the company). Selection at PT. Dua Kelinci Kabupaten Pati, there are several stages that must be followed by prospective employee participants, while the stages are Psychological Test, Initial Interview, FGD (Focus Group Discussion), Interview of Directors. Based on the results of qualitative descriptive analysis at PT. Dua Kelinci Kabupaten Pati, shows that the recruitment and selection process for employees at PT. Dua Kelinci Kabupaten Pati have good criteria according to existing theories and procedures.